Cisplatin induces the release of extracellular vesicles from ovarian cancer cells that can induce invasiveness and drug resistance in bystander cells. (20th November 2017) - Samuel, Priya; Mulcahy, Laura Ann; Furlong, Fiona; McCarthy, Helen O.; Brooks, Susan Ann; Fabbri, Muller; Pink, Ryan Charles; Carter, David Raul Francisco
Abstract : Ovarian cancer has a poor overall survival that is partly caused by resistance to drugs such as cisplatin. Resistance can be acquired as a result of changes to the tumour or due to altered interactions within the tumour microenvironment. Extracellular vesicles (EVs), small lipid-bound vesicles that are loaded with macromolecular cargo and released by cells, are emerging as mediators of communication in the tumour microenvironment. We previously showed that EVs mediate the bystander effect, a phenomenon in which stressed cells can communicate with neighbouring naive cells leading to various effects including DNA damage; however, the role of EVs released following cisplatin treatment has not been tested. Here we show that treatment of cells with cisplatin led to the release of EVs that could induce invasion and increased resistance when taken up by bystander cells. This coincided with changes in p38 and JNK signalling, suggesting that these pathways may be involved in mediating the effects. We also show that EV uptake inhibitors could prevent this EV-mediated adaptive response and thus sensitize cells in vitro to the effects of cisplatin. Our results suggest that preventing pro-tumourigenic EV cross-talk during chemotherapy is a potential therapeutic target for improving outcome in ovarian cancer patients. This article is part of the discussion meeting issue 'Extracellular vesicles and the tumour microenvironment'.